Scientific Meetings 2004-Rpt 98/1(TRSTMH 20) (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2004)
Background Snakebite envenomation is a significant public health problem in rural India, with Tamil Nadu reporting considerable morbidity and mortality. This study assessed the burden, epidemiological patterns and determinants of snakebite deaths using surveillance and verbal autopsy (VA) data. Methods A retrospective analysis of snakebite cases reported under the Integrated Disease Surveillance Programme-Integrated Health Information Platform from January 2022 to May 2025 was conducted. Of the 100 fatal snakebite cases identified, VA was conducted for 40 cases reported between January 2024 and May 2025 to identify factors contributing to mortality. Proportional mortality ratio (PMR), age-standardized mortality rate (ASMR) and autoregressive integrated moving average-based time series forecasting were performed. Results A total of 56 664 cases were reported, with seasonal peaks during June-October. Adults ages 20-60 y (74.4%), males (63.7%) and rural residents (57.2%) were predominantly affected. A total of 100 deaths were reported (case fatality rate 0.18%, ASMR 0.14 per 100 000), lower than national and global estimates. However, elderly adults (PMR 166.5) and females (PMR 126.7) showed disproportionately higher mortality. Deaths commonly occurred among rural agricultural workers and were frequently associated with delayed healthcare access and harmful first aid practices. Conclusions Distinct demographic, seasonal and geographic patterns exist. Targeted risk reduction, improved first-aid awareness and strengthened seasonal preparedness are essential to further reduce mortality and achieve the national goal of halving snakebite deaths by 2030.